A Review of Tsing, Swanson, Gan, and Bubandt’s (2017) Edited Volume: Arts of Living on a Damaged Planet - Tate, Morgan Paige (Art/Research International)

(untitled) (University of Alberta, 2021)
This is a review of Arts of Living on a Damaged Planet: Ghosts and Monsters of the Anthropocene, an edited volume from Anna Tsing, Heather Swanson, Elaine Gan, and Nils Bubandt. The text showcases historical abuses of the earth and offers a myriad of opportunities to creatively inquire about our current relationship and interactions with other matter, creating a sense of urgency within the precarity of the Anthropocene.